2015
DOI: 10.1016/j.reprotox.2015.01.007
|View full text |Cite
|
Sign up to set email alerts
|

The trichloroethylene metabolite S-(1,2-dichlorovinyl)-l-cysteine but not trichloroacetate inhibits pathogen-stimulated TNF-α in human extraplacental membranes in vitro

Abstract: Extraplacental membranes define the gestational compartment and provide a barrier to infectious microorganisms ascending the gravid female reproductive tract. We tested the hypothesis that bioactive metabolites of trichloroethylene (TCE) decrease pathogen-stimulated innate immune response of extraplacental membranes. Extraplacental membranes were cultured for 4, 8, and 24 h with the TCE metabolites trichloroacetate (TCA) or S-(1,2-dichlorovinyl)-L-cysteine (DCVC) in the absence or presence of lipoteichoic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 58 publications
(64 reference statements)
3
15
0
Order By: Relevance
“…Ascension of GBS from the vaginal tract has been observed in both non-pregnant ( 62 ) and pregnant mice ( 172 ) suggesting this is the main route by which GBS compromises placental tissues. GBS stimulates HBD-2, IL-1β, IL-8, IL-10, and TNF-α in human extraplacental or chorioamniotic membranes ex vivo ( 103 , 173 175 ). In a rhesus monkey GBS infection model, increased amniotic fluid TNF-α, IL-1β, and IL-6 occurred before uterine contractility or any clinical signs of infection, suggesting a direct role for infection in triggering preterm labor ( 176 ).…”
Section: Placental Immune Responses To Gbs Infectionmentioning
confidence: 99%
“…Ascension of GBS from the vaginal tract has been observed in both non-pregnant ( 62 ) and pregnant mice ( 172 ) suggesting this is the main route by which GBS compromises placental tissues. GBS stimulates HBD-2, IL-1β, IL-8, IL-10, and TNF-α in human extraplacental or chorioamniotic membranes ex vivo ( 103 , 173 175 ). In a rhesus monkey GBS infection model, increased amniotic fluid TNF-α, IL-1β, and IL-6 occurred before uterine contractility or any clinical signs of infection, suggesting a direct role for infection in triggering preterm labor ( 176 ).…”
Section: Placental Immune Responses To Gbs Infectionmentioning
confidence: 99%
“…Gestational tissues stimulated with GBS produce unique inflammatory cytokine profiles. We previously reported that GBS inoculation ex vivo stimulated secretion of proinflammatory cytokines such as IL1A, IL1B, TNF, and CXCL8 (IL8) from human extraplacental membranes in transwell cultures and from human extraplacental membranes dissected free of amnion [18,19]. Other studies reported similar results, showing that GBS stimulated IL1B, IL6, IL10, and TNF release from human extraplacental membranes [20][21][22].…”
Section: Introductionmentioning
confidence: 70%
“…such as interleukins, tumor necrosis factor, and granulocyte colonystimulating factors [33]. Indeed, multiple studies have reported that GBS stimulates the release of inflammatory cytokines from human extraplacental membranes [18,19,21,22,34]. These cytokines stimulate gestational tissues to produce PGs such as PGE2 and PGF2A [35].…”
Section: Discussionmentioning
confidence: 99%
“…GBS are able to adhere to and invade both chorionic and amniotic epithelial cells [62, 91], which are partially mediated by several factors: 1) IagA, a glycosyltransferase that helps anchor lipoteichoic acid to the cell surface [92], 2) the hemolytic pigment and its regulator CovR/S [62], and 3) quorum sensing mediated by genes in the rgf operon [93]. GBS has also been shown to induce secretion of multiple cytokines and defensins from placental membranes ex vivo , including TNF-α, IL-1α, IL-1β, IL-6, and IL-8 [44, 62, 9496]. Inflammation is stimulated either through pattern-recognition receptor (PRR) sensing of GBS antigens [44, 94] or by pigment-mediated activation of nuclear factor-κB (NF-κB) [62].…”
Section: Host Determinants Of Gbs Vaginal Colonization Ascending Infmentioning
confidence: 99%
“…GBS has also been shown to induce secretion of multiple cytokines and defensins from placental membranes ex vivo , including TNF-α, IL-1α, IL-1β, IL-6, and IL-8 [44, 62, 9496]. Inflammation is stimulated either through pattern-recognition receptor (PRR) sensing of GBS antigens [44, 94] or by pigment-mediated activation of nuclear factor-κB (NF-κB) [62]. An important family of PRRs that mediates placental membrane immunity are the Siglecs [97, 98], a family of cell-surface sialic acid binding lectins that regulate innate and adaptive immune function [99].…”
Section: Host Determinants Of Gbs Vaginal Colonization Ascending Infmentioning
confidence: 99%